You are on page 1of 3

Math 110A: Homework 2 solutions

1.4.4 The temperature function u only depends on x. The equation for the temperature
with the heat source is
u xx = 0

for

u xx + H = 0

for

l
2

0x

l
xl
2

Solving these ODEs, we have that


u ( x ) = c1 x + c2
u( x ) =

for

l
2
l
for
xl
2

0x

Hx2
+ c3 x + c4
2

where c1 , c2 , c3 and c4 are constants. With the boundary conditions at both end
points and the middle point, we have
u (0) = c2 = 0
1 2
u(l ) =
Hl + c3 l + c4 = 0
2
l
1
1 2 1
u ( ) = c1 l + c2 =
Hl + c3 l + c4
2
2
8
2
l
1
u x ( ) = c1 =
Hl + c3
2
2
From the second and fourth equations, we have
c1 l + c4 = 0
Plug this into the third equation, we have
1
c1 l =
2
3c1 =

1 2 1
Hl + c3 l
8
2
1
Hl + c3
4

c1 l

From this and the fourth equation, we can solve for c1 , and consequently c3 and c4 .
c1 =

1
5
Hl, c3 = Hl, c4 =
8
8

1 2
Hl
8

Since u( x ) is increasing for 0 < x < 2l , so the maximum is at x = 2l with u( 2l ) =


1
l
2
0
16 Hl . Now we use calculus to find the maximum for 2 < x < l. If u ( x ) = 0, we
9
1
have that Hx = c3 = 58 Hl, so x = 58 l with u( 58 l ) = 128
Hl 2 > 16
Hl 2 , so this is the
actual maximum over the whole rod.
1

1.5.1 The second order ODE has the characteristic equation r2 + 1 = 0 which has roots i,
so the solution is c1 cos( x ) + c2 sin( x ). Since u(0) = 0, we have c1 = 0, and u( L) = 0
implies c2 sin( L) = 0. If sin( L) 6= 0, we can conclude that c2 = 0 and it follows that
u( x ) = 0 is the unique solution. In contrast, if L = pn for some integer n, then we
cannot solve for c2 and the solution is not unique.
1.5.5 From the method of characteristics, we have that the solution is constant on the
dy
curve defined by dx = y. This has solutions y = Ce x . Therefore, the solution to the
PDE is u( x, y) = f (ye x ) where f is any function.
(a) If u( x, 0) = x, then f (0 e
theres no solution.

x)

= f (0) = x for all x which is not possible, so

(b) If u( x, 0) = 1, then f (0 e x ) = f (0) = 1, the we can choose f ( x ) to be any


function such that f (0) = 1.
2
1
1.6.1 (a)
(1)(2) < 0, so the equation is elliptic.
2
(b)

6 2
2

(9)(1) = 0, so the equation is parabolic.

1.6.2 The discriminant is ( xy)2 (1 + x )( y2 ) = y2 [(y + 1/2)2 + 3/4)] which is always


positive unless y = 0, sothe equation is hyperbolic on the whole plane except on the
x-axis where it is parabolic.
2
4
1.6.4
(1)(4) = 0, so the equation is parabolic. The rest are computations.
2
1.6.5 Let f( x, y) = ax + by. We have a useful fact that for any functions u and v,(uv) xx =
u xx v + 2u x v x + uv xx (and similar identity for the derivative in y). If we let v = ef( x,y) ,
we have
(uef ) xx = u xx ef + 2au x ef + a2 uef .

Now we compare with the given equation. Since there is 2u x , so we want 2a = 2,


that is a = 1. Similarly, since there is 3(uyy + 8uy ), so 2b = 8, that is b = 4. If we
define v = uef , then the new equation that we have is v xx + 3vyy + cv = 0 for some
constant v. The last step is tomake a change of variable y0 = gy for some number g.
By chain rule, we have
dy0
v y = v y0
= gvy0
dy
Consequently, vyy = g2 cy0 . By plugging this in the equation, we have 3g2 = 1 and
so g = p1 .
3

2.1.1 Using the formula,


1
u( x, t) = (e x+ct + e x
2
1
= (e x+ct + e x
2

1 x+ct
)+
sin x dx
2c x ct
1
ct
) + cos( x ) cos(ct).
c
ct

2.1.2 Using the formula,


1
1
u( x, t) = [log(1 + ( x + ct)2 ) + log(1 + ( x ct)2 )] +
2
2c
1
= [log(1 + ( x + ct)2 )(1 + ( x ct)2 )] + 4t + xt.
2

Z x+ct
x ct

(4 + x ) dx

2.1.5 You need to draw the graph in order to solve this problem. Notice that the graph of
y is a rectangle with length 2a from a to a and width 1. Lets call this rectangle A.
R x+ct
Then, the picture of x ct y(s) ds is the area of the intersection between A another
rectangle that goes from x ct to x + ct with width 1. Lets call this one B. There
are three cases that could happen. (1) B is inside A or A is inside of B (depending
on which one is larger). (2) only a part of B overlaps with A. (3) B is outside of A.
a
We will only do the first case as the rest requires the same idea. Let t = 2c
. Then B
a
a
a
is a rectangle from x 2 to x + 2 and the length of B is 2ct = 2c( 2c ) = a. First, we
consider case (1). When the left edge of B hits the left edge of A i.e. x 2a = a, we
have that x = 2a . When the right edge of B hits that of A, we have x + 2a = a, that
is x = 2a . Therefore,
(a) Case (1) happens when

a
2

<x<

a
2

and u( x, t) =

1
2c

area of intersection =

When shifting rectangle B further to the left or to the right, we notice that
a
(a) Case (2) happens when 3a
2 < x <
2 or
1
1
u( x, t) = 2c
( x + 2a ( a)) = 2c
( x + 3a
2)
1
a
1 3a
or u( x, t) = 2c ( a ( x 2 )) = 2c ( 2
x ).

(b) Case (3) happens when x <

3a
2

or x >

3a
2

a
2

<x<

3a
2

with

and u( x, t) = 0.

a
2c .